Exploring anxiety of practicum counselor by using drawing activities - Kassim, Siti Kholijah; Rais, Haniza (2019)
The study explores the anxiety of a group of practicum counselors in order to help them to cope with difficulties and challenges during counseling practicum. The experiences were shared using creative art activity (drawing) during their weekly supervision. Koltz and Odegard (2012), mentioned that using creativity in supervision enables the supervisor to model the counseling concept and gives opportunity for the supervisee or practicum counselor learn during the practicum or internship. The study involved forty practicum counselors who were enrolled in Bachelor of Education Guidance and Counseling program. They were undergoing a 7-week counseling practicum in various areas in Klang Valley. The data revealed that the practicum counselors were facing with various kinds of challenges such as relationship with community, and inability to apply theories into practice.For these challenges, They adopted various kinds of coping strategies to deal with their personal and professional issues. Communicating with friends and university supervisor seems to be an important coping mechanism for them. The study manages to capture various feeling related to their experiences at different phases of the practicum journey (pre, during and post practicum). Through the drawings, they were able to feel more at ease and be more objective in sharing their experiences. The study also confirms the need for continuous support from supervisor and a platform to share their experiences during supervision